Merestorasi Manusia Kota: Memahami Kota Dalam Hukum Tahun Yobel (Im. 25:29-34) Sebagai Sintesis Antara Realitas Dan Utopia - David Pardomuan Sitompul (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2023)
Jubilee Year Law (Lev. 25:8-55) talks about restoring the live of the poor and oppressed among Israelites by handing over the land and the property they had sold before back to them in the Year of Jubilee. However, for the case of properties in a walled city (Lev. 25:29-31), the Law is discriminative to non-Levite Israelites because their properties that had been sold or mortgaged could only be redeemed in term of one year otherwise it would become permanent possession of another person and could not be returned in Jubilee Year. The purpose of this article is to reveal the logical reason why Leviticus 25:29-34 is discriminative and its implication to the life of people living in a city today. For this reason, the author uses a qualitative method with a literature study approach. This article concludes that theological view and demographic reality of that particular time were contradictory that produced contradictory treatment of Jubilee Year Law to both non-Levites and Levites having properties in a walled city as a solution to restore the life of the poor living in cities.